2021
DOI: 10.3390/cancers13174294
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Effect of KRAS Mutations in Non-Small Cell Lung Carcinoma Revisited: A Norwegian Multicentre Study

Abstract: Background: due to emerging therapeutics targeting KRAS G12C and previous reports with conflicting results regarding the prognostic impact of KRAS and KRAS G12C in non-small cell lung cancer (NSCLC), we aimed to investigate the frequency of KRAS mutations and their associations with clinical characteristics and outcome. Since mutation subtypes have different preferences for downstream pathways, we also aimed to investigate whether there were differences in outcome according to mutation preference for the Raf, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…A previous report suggested that among NSCLC patients, White (13.0%) and Black patients (10.9%) had more proportion of KRAS G12C mutations than Asians (3.6%) [ 27 ]. Other studies also confirmed this distribution phenomenon of KRAS G12C mutation [ 28 30 ]. The proportion of KRAS G12C mutation was low in the present study, like the abovementioned research.…”
Section: Discussionsupporting
confidence: 66%
“…A previous report suggested that among NSCLC patients, White (13.0%) and Black patients (10.9%) had more proportion of KRAS G12C mutations than Asians (3.6%) [ 27 ]. Other studies also confirmed this distribution phenomenon of KRAS G12C mutation [ 28 30 ]. The proportion of KRAS G12C mutation was low in the present study, like the abovementioned research.…”
Section: Discussionsupporting
confidence: 66%
“…This contrasts with two large cohorts from France and Germany 10 , 41 but corresponds with other studies. 2 , 8 , 9 , 42 In our study, sex was a significant prognostic factor for OS, as women had a better survival than men which was not explained by differences in patient and tumor characteristics ( p < 0.0001). This was not found in other larger KRAS cohorts, but in these cohorts, patients with stages I to IV NSCLC with different treatment modalities were included, 42 , 43 and our study included only those with stage IV treated with systemic therapy.…”
Section: Discussionmentioning
confidence: 46%
“…ctDNA data was available from three previous studies [ 15 17 ]. In one cohort, tumor tissue DNA was screened for a pathogenic mutation in the gene Kirsten Rat Sarcoma Viral Oncogene Homolog ( KRAS ) [ 18 ]. Tumor tissue DNA in the other cohorts were screened for pathogenic mutations in 22[ 17 ] or 275[ 16 ] genes using next-generation sequencing (NGS).…”
Section: Methodsmentioning
confidence: 99%